Gotcha! A profile of smuggling in international trade - Helge Berger; Volker Nitsch (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2008)
This paper explores official trade data to identify patterns of smuggling in international trade. Our main measure of interest is the difference in matched partner trade statistics, i.e., the extent to which the recorded export value in the source country deviates from the reported import value in the destination country. Analyzing 4-digit product level data for the world's five largest importers for the period from 2002-2006, we find that the reporting gaps are highly correlated with the level of corruption in both partner countries. This finding supports the hypothesis that trade gaps partly represent smuggling activities.
Keywords: D73; F14; F19; O17; O57; 330; Corruption; illicit; illegal; trade; statistics; tariffs; Schmuggel; Außenhandelsstatistik; Export; Import; Internationale Wirtschaftsbeziehungen; Welt